Kritik Sosial dalam Novel Burung Kayu Karya Niduparas Erlang (Tinjauan Sosiologi Sastra): - Arum, Dyah sekar; Amalia, Laili Rizki; Putri, Widya Ryolita (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
This research aims to describe the inner conflicts experienced by the characters in the story novel Burung Kayu Niduparas Erlang's work is based on Soerjono Soekanto's theory of social criticism using a Literary Sociology approach. The research method used is descriptive qualitative. The data source for this research is the novel Burung Kayu by Niduparas Erlang, published by Teroka Press in June 2020 with 174 pages. Data research techniques using reading and note-taking methods and literature. The results of this research are social problems which become a social criticism in the novel Burung Kayu according to Soekanto's theory, namely: violence, war, environmental problems.